Pengaruh Media Pembelajaran KIT IPA Terhadap Motivasi dan Hasil Belajar Siswa Kelas IV - Anisah Aprilia Wahyuningtiyas; Ihwan Firmansyah; Siska Pratiwi (Elementary Teacher Education Program, Majalengka University, 2023)
Based on the results of observations, it can be seen that there are some students whose grades do not reach the KKM score. This happens because the method used by the teacher in learning is only the lecture method. Teachers who are creative in the learning process should immediately provide learning materials using tools in the form of learning media so that the scores of students who are below the KKM will decrease. The purpose of this writing is to determine the effect of KIT IPA learning media on motivation and student learning outcomes in learning. The writing method uses quantitative with the experimental method, namely trying to practice directly related to the material being taught by the teacher. The results that the writer got during the observation process were that there was an increase in the scores obtained by students after the teacher implemented the learning process using media aids. The next suggestion is that teachers can use learning media in schools to help the process of delivering material to students so that students can easily understand the material and are more enthusiastic about learning.